Reproductive strategies of two Curimatidae species in a Mogi Guacu impoundment, upper Parana River basin, São Paulo, Brazil - Peressin, Alexandre [UNESP]; Goncalves, Cristina da Silva [UNESP]; Braga, Francisco Manoel de Souza [UNESP] (Soc Brasileira Ictiologia, 2012)
Considering that reproduction studies are fundamental to understand the life cycle of organisms, this study aimed to investigate the reproductive strategies of saguirus Cyphocharax nagelii and Steindachnerina insculpta in a dam of Mogi Guacu River, (SP). Specimens were collected between August 2005 and July 2006 using gillnets with mesh sizes ranging from 1.5 to 5.0 cm between adjacent knots. Reproductive dynamics, body condition, reproductive period, spawning type and fecundity were analyzed in both species. The body condition reflected the reproductive dynamics, and differed significantly between the wet and dry seasons. During the dry season, the feeding activity and the accumulation of fat in the visceral cavity were higher. The reproductive period of both species covered the months between August and February, with peaks in October and December, and the distribution of the diameters of oocytes allowed to classify them as total spawners. The fecundity increased with weight and length, reaching 28,800 and 27,906 oocytes per female for C. nagelii and S. insculpta, respectively, whereas the amplitude of oocyte diameters varied between 50-1025 mu m for the former and 75-975 mu m for the later species. Taking into account that species with different reproductive strategies also respond differently to environmental impacts, our findings provide important information to subsidize management plans for these curimatid species.

Considerando que o conhecimento da reprodução é fundamental para a compreensão do ciclo de vida dos organismos, este trabalho buscou avaliar as estratégias reprodutivas dos saguirus Cyphocharax nagelii e Steindachnerina insculpta em um represamento no rio Mogi Guaçu (SP). Os exemplares foram coletados entre agosto de 2005 e julho de 2006 com redes-de-espera (com tamanhos de malha variando entre 1,5 e 5,0 cm entre nós adjacentes). A dinâmica reprodutiva, a condição corporal, o período reprodutivo, o tipo de desova e a fecundidade foram os parâmetros reprodutivos analisados nas duas espécies. A condição corpórea refletiu a dinâmica reprodutiva, sendo significativamente diferente entre os períodos seco e chuvoso. Durante o período seco, a atividade alimentar e o acúmulo de gordura na cavidade visceral foram maiores. O período reprodutivo das duas espécies abrangeu os meses entre agosto e fevereiro, com picos em outubro e dezembro, e a distribuição dos diâmetros de ovócitos permitiu classificá-las como desovadoras totais. A fecundidade aumentou com o peso e com o comprimento, atingindo em média 28.800 e 27.906 ovócitos por fêmea, para C. nagelii e S. insculpta, respectivamente, ao passo que a amplitude de diâmetros ovocitários variou de 50 a 1.025 µm para a primeira e de 75 a 975 µm para a segunda espécie. Considerando que espécies com estratégias reprodutivas diferentes também respondem de modos diferentes aos impactos ambientais, as informações obtidas são importantes subsídios para nortear medidas de manejo para essas espécies de curimatídeos.
Keywords: Cyphocharax; Fecundity; Spawning; Steindachnerina; Toothless characin